(a+b)^3-(a-b)^3=((a+b)-(a-b)(a+b)^2+(a^2-b^2)+(a-b)^2)= дальше как
(a+b)^3-(a-b)^3=((a+b)-(a-b)(a+b)^2+(a^2-b^2)+(a-b)^2)= дальше как
Ответ(ы) на вопрос:
Есть формула сокращенного умножения (разность кубов):
a^3-b^3=(a-b)(a^2+ab+b^2). Используя ее получаем:
(a+b)^3-(a-b)^3=(a+b-a+b)(a^2+2ab+b^2+a^2-b^2+a^2-2ab+b^2)=
=2b(3a^2+b)
Вроде так
[latex](a+b)^3-(a-b)^3=((a+b)-(a-b))((a+b)^2+(a^2-b^2)+ \\ (a-b)^2)=(a+b-a+b)(a^2+2ab+b^2+a^2-b^2+a^2-2ab+b^2)= \\ 2b(3a^2+b^2)=6a^2b+2b^3[/latex]
Не нашли ответ?
Похожие вопросы